Fetal status and perinatal outcomes in placenta previa - Yu. N. Fatkullina; A. G. Yashchuk; A. Yu. Lazareva; N. A. Stetsenko; N. A. Tadzhiboeva; L. A. Fayzullina (IRBIS LLC, 2022)
Introduction. Obstetric hemorrhage associated with placental abnormalities holds a leading place in the pattern of massive hemorrhage and maternal mortality, have been increasingly relevant due to the elevating rate of abdominal delivery.Aim: to assess fetal condition, parameters of uteroplacental and fetal hemodynamics as well as perinatal outcomes in pregnancy complicated with placenta previa.Materials and Methods. The retrospective study included 112 women aged 18-38 years who performed delivery between January 2016 and September 2020. Two groups were formed: the main group - 42 patients with placenta previa, and the control group - 70 pregnant women with normal placentation. Examination of women was carried out at admission for delivery within the gestational age between 26 to 40 weeks. We studied the parameters of fetometry and dopplerometry, hemogram parameters, biochemical blood analysis and some hemostasis parameters.Results. The groups examined were comparable in age and anthropometric data. In the main vs. control group, the course of pregnancy was more often complicated by the threatened termination (45 % vs. 21 %; p = 0.03), anemia (hemoglobin level 107 g/L vs. 110 g/L; p = 0.044), fetal growth retardation. Assessment of uteroplacental state and fetal-placental blood flow revealed differences indicating the presence of pathophysiological basis for developing hypotrophy and fetal hypoxia in the group of women with placenta previa. In the main group, the average gestational age at the time of delivery was 35.0 ± 2.8 weeks, in the control group - 39.0 ± 1.3 weeks (p = 0.003). Delivery showed significantly increased risk of preterm birth and rate of neonatal respiratory disorders in the main group.Conclusion. The results obtained evidence about a need to provide a careful approach to manage pregnant women with placenta previa to timely prevent anemia, placental disorders and hypotrophy. At the stage of the level III obstetric hospital, it is necessary to be ready for decompensation of placental disorders, birth of children with respiratory disorders, and fetal growth retardation.